Rumah Sakit Kanker Di Pekanbaru Dengan Pendekatan Healing Environment - Shodiqin, Muhammad Zikri; Hidayat, Wahyu; Aldy, Pedia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Cancer is a disease that experiences abnormal, fast and uncontrollable growth and threatens the lives of individual sufferers, this is evidenced by the increasing number of cancer patients annually. The province of Riau itself sufferers of the cancer ranks to 4 by 0.7% orapproximately 4,301 inhabitants. From these problems, a special action and a response to cancer is required. Meanwhile, in Riau, especially the city of Pekanbaru health facilities are still not adequate, so from this problem arise idea to improve the adequate health means andhave a special quality of service treating cancer sufferers With the design of cancer hospital in Pekanbaru. The method used in this design is to use the Healing Environment approach by applying the principles and design ideas that exist in this cancer hospital. The concept used isthe ribbon symbol caring for cancer because it symbolizes caring, support empathy, understanding and love.Keywords : Healing Environment, Cancer, Hospital, Pekanbaru